Mucor pulmonary embolism in a patient with myelodysplastic syndrome. (2020) - Kakuwa, T.; Ariga, A.; Takasaki, J.; Kato, M.; Igari, T.; Shida, Y.; Okafuji, T.; Nakamura, S.; Miyazaki, Y.; Katano, H.; Iikura, M.; Izumi, S.; et al.
Abstract: Mucormycosis is a life-threatening infectious disease that occurs most commonly in immunocompromised patients such as those with hematological malignancies. Its clinical symptoms and associated radiological findings vary and specific biomarkers and culture characteristics have not been defined. An 85-year-old man who had been treated for myelodysplastic syndrome and tuberculosis for several months presented with subacute fever and worsening left-side chest pain. Contrast-enhanced computed tomography images depicted massive tumor-like consolidation without enhancement, expanding from the left lower lobe. Emboli that did not respond to anticoagulants were detected in the left descending pulmonary artery. Despite intensive treatment he developed multiple organ failure and died 47 days after hospitalization. Gross pathology of a lung autopsy specimen revealed left lower pulmonary arterial emboli and pulmonary infarction, which was concluded to be the direct cause of death. The emboli were histopathologically identified as invasive mycelia in vessels. Mucor sp. was detected via real-time polymerase chain reaction and immunohistopathological analyses revealed that the mold in the blood vessels of lung tissue was partially positive for the mucor antigen. In the present case of Mucor sp. pulmonary emboli in a patient with myelodysplastic syndrome, radiographic findings were hard to distinguish from those typical of a lung abscess.